Electromagnetic Study of Ethylene Glycol and FC-75 for an RF Window - Singh A.S.; Rao S.V. (My University, 2025)
In this paper, the reflectivity of coolants is studied to design an RF window to VEDs in the megawatt-class operating regime. Two coolants ethylene glycol (EG) and FC-75 are investigated to design a 10 GHz RF window for megawatt-class operation. EG and FC-75 are employed in between two dielectric discs of aluminum nitride (AlN). Modeling and Electromagnetic study of RF windows with coolants are studied using finite integration technique based 3D simulation tool CST microwave studio. RF propagation characteristics study of RF window (EG) predicts S11 of -19 dB and S21 of -3 dB while RF window with FC-75 possesses S11 of -30 dB and S21 of -0.07 dB. © 2020 URSI.